Diabetes mellitus and risk of brain tumors: A meta-analysis - TONG, JIAO JIAN (D.A. Spandidos, 2012)
Accumulating evidence suggests that a history of diabetes may be involved in the occurrence of various types of cancer. However, the association of diabetes with the risk of brain tumors remains unclear. We identified relevant studies by performing a literature search of PubMed and EMBASE (through to 24 May 2012) and by searching the reference lists of pertinent articles. All data were extracted independently by two investigators using a standardized data abstraction tool. Summary relative risks (SRRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Inter-study heterogeneity was assessed using the Cochran’s Q and I(2) statistical tests. A total of 13 studies were included in this meta-analysis, including the entire Danish population, 5,107,506 other participants and more than 2,206 cases of brain tumors. In the analysis of these 13 studies, we observed that diabetic individuals had a similar risk of brain tumors as non-diabetic individuals (SRR, 1.12; 95% CI, 0.89–1.42). There was significant evidence of heterogeneity among these studies (P<0.001; I(2), 93.5%). Sub-group analysis revealed that diabetic females had a 24.2% increased risk of brain tumors (SRR, 1.242; 95% CI, 1.026–1.502), which was not observed in diabetic males. No significant publication bias was found in this study. The findings of this meta-analysis indicate that diabetic individuals have a similar risk of brain tumors as non-diabetic individuals. However, a significant positive correlation between the risk of brain tumors and diabetes mellitus was revealed in females, but not in males.